Solvability and asymptotic properties for an elliptic geophysical fluid flows model in a planar exterior domain - Zhang, Xinguang; Liu, Lishan; Wu, Yonghong; Wiwatanapataphee, B.; Cui, Yujun (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we study the solvability and asymptotic properties of a recently derived gyre model of nonlinear elliptic Schrödinger equation arising from the geophysical fluid flows. The existence theorems and the asymptotic properties for radial positive solutions are established due to space theory and analytical techniques, some special cases and specific examples are also given to describe the applicability of model in gyres of geophysical fluid flows.
Keywords: gyres of geophysical fluid flows; Schrödinger equations; asymptotic properties; radial positive solutions